Music Therapy in Children with Autism Spectrum Disorder: What and How - Irene Cathrin Shalomnita Hale; Farida Kurniawati (Faculty of Psychology Universitas Gadjah Mada, 2022)
Until now, music therapy is still widely used to help children with autism. In this literature study, various music therapy research will be explained and explicitly given to help children with an autism spectrum disorder. This literature study using two academic electronic search engines: Taylor Francis Online dan EBSCOhost Academic Research Database. For this literature study, researcher using five research studies from abroad, and three research studies from Indonesia. Besides, this literature study is expected to help parents with autistic children, children with needs precisely, as well as music therapists, to get information about the types of therapy and to get therapy music choices that fit the goals to be achieved.